(untitled) (Педагогіка вищої та середньої школи, 2022)
In times of studies in an institute of higher students must capture the system of major pedagogical and subject knowledges, abilities and skills which provided skilled implementation оf professional activity. Various approaches in relation to forming оf professional pedagogical abilities at future teachers are examined in the article.